Endogenous Leucine-Rich Repeat Kinase 2 Slows Synaptic Vesicle Recycling in Striatal Neurons - Maas, James W. Jr.; Yang, Jing; Edwards, Robert H. (Frontiers in Synaptic Neuroscience, 2017)
Dominant mutations in leucine-rich repeat kinase 2 (LRRK2) produce the most common inherited form of Parkinson’s disease but the function of LRRK2 remains poorly understood. The presynaptic role of multiple genes linked to PD including α-synuclein has suggested that LRRK2 may also influence neurotransmitter release, a possibility supported by recent work. However, the use of disease-associated mutants that cause toxicity complicates the analysis. To determine whether LRRK2 normally influences the synaptic vesicle, we have now used a combination of imaging and electrophysiology to study LRRK2 knockout mice. Surprisingly, we find that in hippocampal neurons, the loss of LRRK2 does not affect synaptic vesicle exocytosis, endocytosis or the mobility of α-synuclein. Double knockout mice lacking LRRK1 as well as LRRK2 also show no defect in transmitter release by hippocampal neurons. However, in striatal neurons, which express LRRK2 at higher levels, the loss of LRRK2 leads to modest acceleration of synaptic vesicle endocytosis. Thus, endogenous LRRK2 normally slows synaptic vesicle recycling at striatal terminals.